Analisis Kelayakan Usahatani Padi Pada Kelompok Tani Samirukun di Kabupaten Sidoarjo: Feasibility Analysis of Rice Farming in the Samirukun Farmer Group in Sidoarjo Regency - Setiawan, Risqi Firdaus; Fitriana, Nisa Hafi Idhoh (Jurnal Ilmiah Manajemen Agribisnis, 2023)
This research aims to analyze production costs, revenues, profits and the feasibility of rice farming in Sidoarjo Regency. This research method uses descriptive sampling technique using the census method for the Samirukun farmer group, Sidoarjo Regency, totaling 29 people. Based on the research results that have been described, it can be concluded that the Samirukun Farmers Group in Sidoarjo Regency pays rice farming costs on average IDR 29,979,094.8 per 1.04 hectare area of cultivated land, with an average income of IDR 39,664,000 and an average profit of IDR 39,664,000. average IDR 9,684,905 per cultivated land area of 1.04 hectares. The results of the farming feasibility analysis with the R/C Ratio were 1.32 and showed that rice farming in Sidoarjo Regency was worth running.